Penerapan Metode Eklektik pada Pembelajaran Bahasa Arab Siswa Kelas VI SDIT Anak Sholeh Mataram - Ayatullah ayatullah (LP2M STIT Palapa Nusantara, 2016)
The purpose of this study was to determine the role of the Arabic language teachers in applying the eclectic method in class VI SDIT Mataram pious child. This study uses a qualitative approach. To collect data using the method of observation, interviews and documentation. As for the analysis, the author uses descriptive qualitative analysis techniques, namely the form of data that is written or spoken of observation and learning activities so that in this case the author seeks to conduct research that is both thorough portrait of the real situation. The results of this study indicate that the application of the eclectic method in teaching Arabic language teachers use to facilitate the teaching-learning process in the classroom. In addition, the eclectic method can depict a variety of teaching methods more effective Arabic language, so that students do not get bored in receiving the material being taught.